Arctic and Antarctic sea ice, 1978-1987 : satellite passive-microwave observations and analysis - Gloersen, Per.; United States. National Aeronautics and Space Administration. Scientific and Technical Information Program. (Washington, D.C. : Scientific and Technical Information Program, National Aeronautics and Space Administration, 1992)
Includes index. Shipping list no.: 93-0645-P. Includes bibliographical references (p. 213-223). Mode of access: Internet.